Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

Introduction : la voix d’Ana Sokolović - Goldman, Jonathan (Circuit, 2012)

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.

Cartographie de l’apprentie - Messier, Anne (Circuit, 2012)
La compositrice québécoise Ana Sokolović est d’origine serbe et plusieurs de ses oeuvres font référence à son pays d’origine, que ce soit par l’utilisation de mélodies et de rythmes traditionnels ou par des références culturelles. Pour approfondir son héritage serbe, l’auteure s’est entretenue avec la compositrice en mars 2012. L’article relate les paysages de son enfance et de son adolescence, l’environnement musical, culturel et politique de ses années d’apprentissage. Le portrait de sa vie familiale et de son quotidien nous permet de saisir des éléments constituants de sa personnalité d’artiste en devenir. Sa décision de s’établir à Montréal est explorée et elle raconte comment elle a pris conscience de son héritage slave.

« J’aime quand on explose de joie ! » : entretien avec Ana Sokolović - Panneton, Isabelle (Circuit, 2012)
Lors d’un entretien réalisé par la compositrice Isabelle Panneton, Ana Sokolović discute de ses inspirations, de ses méthodes et de son rapport avec les interprètes de sa musique.

L'intuition de/dans l'œuvre de la compositrice québécoise Isabelle Panneton: un défi à la bipartition du genre - Stévance, Sophie (Le genre à l'œuvre, 2012)

Violet Archer's "The Twenty-Third Psalm" (1952): An Analytical Study of Text and Music Relations Through Fibonacci Numbers, Melodic Contour, Motives, and Piano Accompaniment - Wan, Jessica Jane (Université d'Ottawa, 2012)
This study explores text and music relations in Canadian composer Violet Archer's “The Twenty-Third Psalm” by analysing the text of Psalm 23, Fibonacci numbers, melodic contours, motives, and the role of the accompaniment. The text focuses on David's faith in God and his acceptance of God as his shepherd on earth. The four other approaches allow us to examine the work on three different structural levels: background through Fibonacci numbers, middleground through melodic contour analysis, and foreground through motivic analysis and the role of the accompaniment. The measure numbers that align with Fibonacci numbers overlap with some of the melodic contour phrases, which are demarcated by rests, as well as with the most important moments at the surface level, such as the emphasis on the word “death” through recurring and symbolic motives. The piano accompaniment further supports these moments in the text.
Keywords: Archer; Canadian music; Communication and the arts; Fibonacci numbers; Melodic contour; Motivic analysis; Music analysis; Psalm 23; Text and music relations; The Twenty-Third Psalm (1952); Theory; Violet